Efficacy and safety of tyrosine kinase inhibitors plus PD-1 inhibitor in patients with transarterial chemoembolization- refractory hepatocellular carcinoma: a two-center retrospective study - Gao, Ya; Lu, Haohao; Xiong, Zhifan (Frontiers in Oncology, 2023)
Object To investigate the efficacy and safety of tyrosine kinase inhibitors (TKIs: sorafenib and lenvatinib) plus PD-1 inhibitor (camrelizumab) versus TKIs alone in transarterial chemoembolization-refractory (TACE-refractory) hepatocellular carcinoma (HCC). Materials and methods Data of TACE-refractory HCC patients treated with TACE+TKIs+PD-1 inhibitor (TACE+TKIs+PD-1group) (n=57) or TACE+TKIs (TACE+TKIs group) (n=50) from January 2019 to January 2022 were retrospectively collected and analyzed. The differences in overall survival (OS), progression-free survival (PFS), tumor responses (based on modified Response Evaluation Criteria in Solid Tumors) and adverse events (AEs) were compared between the two groups. Potential factors affecting OS and PFS were evaluated by univariate and multivariate analyses. Results Compared with the TKIs group, both PFS and OS were prolonged in the TACE+TKIs+PD-1 group (median PFS: 7 months vs. 5 months, P=0.007; median OS: 17 months vs. 11 months, P=0.002). In multivariate analysis, tumor size and treatment were independent prognostic factors for PFS and OS. The incidence and severity of AEs related to the treatment between the two groups showed no significant difference. Conclusion The treatment of TACE combined with TKIs plus camrelizumab demonstrated promising efficacy and safety in TACE-refractory HCC.